JUSTICE AS CRY OF THE EARTH: The Book of Revelation in Shin Megami Tensei: Devil Survivor 2 - C. Peracullo, Jeane (Journal of Dharma, 2014)
The article explores the apocalyptic themes in a popular Japanese video game, Shin Megami Tensei: Devil Survivor 2 by juxtaposing it with The Book of Revelation. Apocalypse means “a vision.” The Book of Revelation is the most widely held epitome of visions and dreams, which is paradoxically about the end, and hope for the salvation, of the world. Devil Survivor 2 alludes to the biblical apocalypse through the preponderance of sevens. A close reading of both The Book of Revelation and Devil Survivor 2 reveals that suffering is a result of believing that only ourselves matter, when we lack compassion towards other people, including earth, and when we do not hear the cries of those who have been robbed, and left to die, by the roadside. Justice for earth is construed as the end of suffering that marks a “new heaven and a new earth.”